2019
DOI: 10.1021/acsapm.9b00103
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Properties of Donor–Acceptor–Donor′ Asymmetric Structured Electrochromic Polymers Based on Fluorenone as Acceptor Units

Abstract: Two novel conjugated polymers based on a donor–acceptor–donor′ (D–A–D′) asymmetric structure, using fluorenone as the acceptor unit linked with different donor units on both sides, were designed and synthesized, namely poly2-(2,3-dihydrothieno­[3,4-b]­[1,4]­dioxin-5-yl)-7-(thiophen-2-yl)-9H-fluoren-9-one (PSWE) and poly2-(4-(diphenylamino)­phenyl)-7-(thiophen-2-yl)-9H-fluoren-9-one (PSWT). Compared with the symmetrical structure polymer poly­(2,7-dithiophen-2-yl)-fluoren-9-one (PSWS), the asymmetric structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Raman responses were influenced by the change of bond polarity, which were related to the changes in electron distribution. C=O has a strong electron absorption effect and ESP distribution showed that the conjugate structure was favorable for the flow of electrons to C=O, [20] and which was proved by our calculation of Mulliken atomic charges (Table S1, Supporting Information). Furthermore, it was found from theory calculations that the extension of the conjugated molecules with chain length longer than 3 had no obvious gain for C=O local charge distribution.…”
Section: Resultssupporting
confidence: 57%
“…Raman responses were influenced by the change of bond polarity, which were related to the changes in electron distribution. C=O has a strong electron absorption effect and ESP distribution showed that the conjugate structure was favorable for the flow of electrons to C=O, [20] and which was proved by our calculation of Mulliken atomic charges (Table S1, Supporting Information). Furthermore, it was found from theory calculations that the extension of the conjugated molecules with chain length longer than 3 had no obvious gain for C=O local charge distribution.…”
Section: Resultssupporting
confidence: 57%
“…For the six conjugated polymers, the good linear relationship between current densities and potential scan rates is observed, which indicates their redox process are nondiffusion-controlled. 43,44 Also, the redox properties of these conjugated polymers were measured under the same conditions at low potential scan rate of 50 mV s −1 (Figure 4c). For poly(ProDOT-Me), the slight oxidation signal could be observed at −0.2 V; however, the obvious oxidation signal appears at about 0.35 V. The result is ascribed to that the surface of poly(ProDOT-Me) could be oxidized at low potential and achieved full oxidation at high potential.…”
Section: Acs Appliedmentioning
confidence: 99%
“…Reynolds et al reported a dual n-and p-type electrochromic device based on poly-(bisEDOT-PyrPyr-Hx2) that was extremely stable [ 29 ]. Zhang and colleagues synthesized two donor–acceptor–donor′ (D–A–D′) asymmetric ECPs, PSWE and PSWT, that outperformed symmetrical D–A–D PSWS in terms of optical contrast, response time, and coloration efficiency [ 30 ]. Toppare et al presented asymmetric thiophene−benzothiadiazole−3, 4-ethylenedioxythiophene type ECP with a 1.18 eV bandgap, exhibiting p- and n-type doping superior to that with symmetrical analogues [ 31 ].…”
Section: Introductionmentioning
confidence: 99%